Postoperative changes in body composition - comparison of bioelectrical impedance analysis and magnetic resonance imaging in bariatric patients - Otto, Mirko; Haneder, Stefan; Michaely, Henrik J. M.; Kienle, Peter; Hasenberg, Till (Obesity surgery, 2015)
Background: Roux-en-Y gastric bypass (RYGB) result in a marked reduction of body fat and also visceral fat (VF) decrease up to 36 % in 16 weeks. This leads to positive effects on cardiometabolic risks, which are known to be correlated with the occurrence of VF. This study analyzed the validity of bioelectrical impedance analysis (BIA) for determining VF in the postoperative course. In addition, magnetic resonance imaging (MRI) was performed for prediction of whole VF in bariatric patients on the basis of a single slice. Methods: Eighteen patients, who underwent RYGB (18), were included in this study. MRI and BIA measurements were performed 1 day before surgery, as well as 6, 12, and 24 weeks after surgery. Results: During the postoperative observation period, we found a significant decrease of both subcutaneous fat (SF) and VF. SF measured by MRI was highly correlated with the level of body fat shown by BIA. In contrast, the VF volume, as determined by MRI, showed no correlation with the body fat measured by BIA. In addition, we were able to show a significant correlation between MRI measured VF volume and the particular single-layer fat area. Conclusions: Compared to the widely used bioelectrical impedance analysis to measure changes in body composition after bariatric procedures, a single-layer MRI was superior in determining VF. Single-layer MRI may be a better tool to recognize changes of VF after bariatric procedures.